Molecular phylogeny of long-tailed giant rats (Muridae: genus leopoldamys) based on mitochondrial cytochrome B sequences - Mohamad Azam Firdaus Saarani; Yong, Hoi-Sen; Badrul Munir Md-Zain; Leonard, Jennifer A.; Hasmahzaiti Omar (Universiti Kebangsaan Malaysia, 2023)
Two species of Leopoldamys long-tailed giant rats are found in Peninsular Malaysia. They are currently referred to as Leopoldamys ciliatus which inhabits montane habitat, and Leopoldamys vociferans which usually inhabits the lowland forest. To date, there is no report on the phylogenetic relationship of L. ciliatus with the other Leopoldamys taxa. The present study was carried out to determine its relationship, based on the mitochondrial cytochrome b (cyt b) gene sequence, with L. vociferans of Peninsular Malaysia and other congeners. Phylogenetic analysis shows that L. ciliatus is a sister-species to the lineage L1 of L. herberti and L. revertens, and is distantly related to L. edwardsi. L. vociferans, and L. sabanus form a distinct clade (lineage L5) from the other Leopoldamys taxa from Indochina. The Sumatra taxon currently known as L. sabanus is genetically distinct to L. vociferans with K2P distances between 0.065 and 0.069. Contrary to previous opinions, L. herberti, L. revertens, and L. neilli of Indochina are valid species based on more than 2.5% threshold genetic distance. Both the L. edwardsi and L. neilli species complexes are represented by several sibling species. A more extensive taxon sampling from various regions (particularly Sumatra and other regions of Indonesia) as well as the use of morphological and molecular (mitogenomes or multiple genes) data sets are needed to provide a robust phylogeny and systematics.